2007
DOI: 10.1002/ajh.20900
|View full text |Cite
|
Sign up to set email alerts
|

The accuracy of activated partial thromboplastin times when drawn through a peripherally inserted central catheter

Abstract: The peripherally‐inserted central catheter (PICC) is used commonly in hospitalized patients. The presence of heparin within the PICC lumen, however, may affect the results of coagulation indices when measured on blood drawn through it. In 41 patients with a PICC inserted as part of their medical care, we compared activated partial thromboplastin times (aPTTs) measured on blood drawn through the PICC to blood drawn through a peripheral venipuncture (VP). There were no clinically significant differences between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…An exception exists for heparinized CVCs, which provided different results in coagulation, considering the partial thromboplastin time, prothrombin time, and fibrinogen activation 24–28 . However, a more recent study provided evidence on the equivalence of coagulation testing from PICCs versus venipuncture 29 …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…An exception exists for heparinized CVCs, which provided different results in coagulation, considering the partial thromboplastin time, prothrombin time, and fibrinogen activation 24–28 . However, a more recent study provided evidence on the equivalence of coagulation testing from PICCs versus venipuncture 29 …”
mentioning
confidence: 99%
“…[24][25][26][27][28] However, a more recent study provided evidence on the equivalence of coagulation testing from PICCs versus venipuncture. 29 Although blood collection by central lines is recommended to reduce anxiety, skin irritation, and superficial bleeding risk, 30 clinicians often request venipuncture to obtain accurate serum antibiotic levels, even if a CVC is inserted. 31 Moreover, as many healthcare professionals believe that blood collected from central lines is affected by medication or fluids administered via the central line, they decide to draw blood by venipuncture to not influence the accuracy of laboratory values.…”
mentioning
confidence: 99%
“…These findings correlated with the results of Farjo's study 1 at York Hospital, which indicated that no consistent standard of practice for collecting CVAD blood specimens was in place across 7 units in the same hospital. Further review of institutional and laboratory policies, [2][3][4] national standards, [5][6][7] manufacturers'guidelines 8,9 (Table 2), previous research studies, [10][11][12][13][14][15][16][17][18][19][20][21][22] and expert opinion 23 ( As discard volume increased, paired aPTT results became increasingly similar, but even with a 9-mL discard, the vascular access device results were not considered clinically trustworthy aPTT results from a CVAD lumen infusing crystalloid (without heparin) were as reliable as those from venipuncture Blood sampling from a multilumen catheter should be done with all intravenous infusions turned off Statistically significant difference between peripheral and CVAD specimens even with 25-mL discard States this is not always clinically significant Prothrombin time and aPTT values were significantly prolonged in samples collected from CVAD when compared with simultaneous peripherally collected samples Accurate samples cannot be collected from a heparinized CVAD With no waste or 10 mL waste, aPTT values significantly prolonged compared with phlebotomy specimens (both P < .001)…”
mentioning
confidence: 99%